Recession: Strengthening The Company’s Foundation With External Environmental Analysis In The Face Of Economic Uncertainty - Gunawan Aji; Amalia Fakhru Nisa; Fitriana Fitriana; Siti Nurlela (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The world economic situation from 2010 to 2012 was full of uncertainties. However, the uncertainty of the global economic situation is expected to remain at a high level and have an impact on falling world commodity prices as a result of weakening world trade. In addition, significantly the current business environment is undergoing complex changes. Thus, business uncertainty (turbulence) is increasingly real. This study uses the literature method in examining more deeply the problems that will be discussed. This study describes the importance of external analysis in facing a recession. The results of the study show that the company or organization assisted by the company can formulate the right strategy by considering the threats and opportunities from the recession problem that has occurred.